Optoelectronics (IntechOpen, 2023)
Optoelectronics - Advanced Materials and Devices is a second edition following the initial Optoelectronics - Materials and Techniques book published in 2011 as part of the InTech collection of international works on optoelectronics. Optoelectronics, as the discipline devoted to the study and application of electronic devices that emit, detect, and otherwise control light, has widely proliferated globally and enabled many of today's modern conveniences. Because of this ubiquity, new applications and novel optical phenomena continue to drive innovation. Accordingly, as with the first book of the collection, this book covers recent achievements by specialists around the world. The growing number of countries participating in this endeavor including now Brazil, Canada, China, Egypt, France, Germany, India, Italy, Japan, Malaysia, Mexico, Moldova, Morocco, Netherlands, Portugal, Romania, Saudi Arabia, South Korea, Taiwan, Ukraine, USA, and Vietnam as well as joint participation of the US and Moldova scientists in edition of this book and writing one of its Chapters testify to the unifying effect of science. An interested reader will find in the book the description of properties and applications employing organic and inorganic materials, such as different polymers, oxides and semiconductors, as well as the methods of fabrication and analysis of operation and regions of application of modern optoelectronic devices.